2016
DOI: 10.1007/s13187-016-1105-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinician and Parent Perspectives on Educational Needs for Increasing Adolescent HPV Vaccination

Abstract: Introduction Human papillomavirus (HPV)-related morbidity and mortality remain a significant public health burden despite the availability of HPV vaccines for cancer prevention. We engaged clinicians and parents to identify barriers and opportunities related to adolescent HPV vaccination within a focused geographic region. Methods This mixed methods study design used an interviewer-administered semi-structured interview with clinicians (n=52) and a written self-administered survey with similar items complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…This indicates an important area for improvement because recent research shows engaging in these high quality recommendation practices significantly increases vaccination rates. 16 Consistent with previous research, 13,14,24,25 education for parents/adolescents and providers was often mentioned by our participants as a necessary step to increase vaccination rates among adolescents. Physicians believed that it would be important to provide education for adolescents by the school system during health and wellness classes.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This indicates an important area for improvement because recent research shows engaging in these high quality recommendation practices significantly increases vaccination rates. 16 Consistent with previous research, 13,14,24,25 education for parents/adolescents and providers was often mentioned by our participants as a necessary step to increase vaccination rates among adolescents. Physicians believed that it would be important to provide education for adolescents by the school system during health and wellness classes.…”
Section: Discussionsupporting
confidence: 86%
“…28 Results of this study found that physicians believe educational media campaigns targeting parents and physicians would help to counter the misinformation about vaccination on social media and would be an important facilitator of HPV vaccination and cancer prevention, which aligns with previous research conducted among a sample of physicians and parents. 25 Our participants also felt more educational media campaigns focusing on vaccine efficacy may positively influence parental perceptions and decrease the Adolescent education "Education for teens regarding vaccine benefits" "Patient handouts in waiting rooms" "Ads in magazines that parents and teens are reading" Parent education "Improve or create online resources that present accurate information for families who are considering the vaccine." "Educate parents on [HPV vaccine] efficacy and side effects" Provider education "Educate doctors on these 2 factors (I always tell my patients this): -HPV affects 80% of men & women by age 50.…”
Section: Discussionmentioning
confidence: 98%
“…The main activities used to influence clinical and health professionals were provision of educational materials, professional education, and protocols to track and report vaccination rates. These activities are in line with research, which indicates that educational campaigns directed at health care professionals and parents are key facilitators for promoting HPV vaccination ( 14 ). Examples of educational efforts to raise awareness about HPV and HPV vaccination are media campaigns, printed materials, online information, webinars, conferences, and in-person training sessions.…”
Section: Discussionsupporting
confidence: 78%
“…Studies have shown that parents and patients want additional information about HPV and the HPV vaccine and that they trust the information provided by health care providers ( 20 ). Providers need additional training on how to give a strong, clear recommendation and communicate the urgency and importance of HPV vaccination ( 14 ). Other potential strategies for providers and health care systems to increase HPV vaccination rates are reducing missed clinical opportunities and administering the HPV vaccine at the same time as other adolescent vaccines ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…56 Similar results were found with interviews and surveys with parents and clinicians in western New York, such that they felt parents needed more and better education about the vaccine to counter the spread of misinformation on social media. 58 An evaluation of a national school-based HPV vaccination campaign for young girls in South Africa in April 2014 found that, while the campaign was able to get 86.6% of age-eligible girls vaccinated, campaign staff reported that misinformation and negative rumors spread via social media during the campaign may have hindered their ability to gain higher vaccination rates because of its perceived negative impact on parental consent by campaign staff. 61 They recommended carefully monitoring social media messaging during campaigns in the future to monitor its influence and be prepared to combat misinformation with a designated media response plan.…”
Section: Concern For Impact Of Negative Information On Social Mediamentioning
confidence: 99%